Carbon neutrality implication of material productivity, total factor productivity and renewable energy uptake in the Nordics - Celik, Ali; Kostekci, Ahmet; Alola, Andrew Adewale (Elsevier, 2024)
The recent report of the European Commission (EC) indicates that the Nordic countries, especially Denmark, Finland, Iceland, Norway, and Sweden have some of the highest and above European Union (EU)'s average consumption per capita of domestic material. While reflecting on the environmental consequence of material uptake, this study examines the role of material productivity, total factor productivity, and renewable energy uptake in the region over the period 1970-2019. With the series of empirical approaches deployed for the panel investigation, the results establish that a gain in material productivity and total factor productivity mitigates carbon emission in the region by a statistically significant amount, thus indicating a positive sign toward green productivity/output and environmental sustainability. This evidence is also complimented by the validity of the environmental Kuznets curve (EKC) i.e., inverted U-shaped nexus between economic output and environmental degradation in the investigation. Moreover, the results reveal that uptake in renewable energy usage also improves environmental quality arising from the energy source's capacity to reduce carbon emission. The findings in this investigation offers relevant policy reference toward improving material and resources efficiency.
Keywords: Resource efficiency; Renewable energy; Environmental quality; Nordic region; Panel analysis